2020
DOI: 10.2147/ott.s259336
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Non-Coding RNA NCK1-AS1 Serves an Oncogenic Role in Gastric Cancer by Regulating miR-137/NUP43 Axis</p>

Abstract: Introduction: Long non-coding RNA (lncRNA) NCK1-AS1 could regulate multiple cancer progression. However, little is known regarding the roles and acting mechanisms of NCK-AS1 in gastric cancer (GC) progression. This work was aimed to explore the relationship between NCK1-AS1 and GC progression to illustrate the mechanisms of NCK1-AS1. Methods: NCK1-AS1 expression level in GC tissues and cells was measured with a quantitative real-time PCR method. In vitro experiments including cell counting kit-8 assay, colony … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…MiR-137-3p (i.e., miR-137) plays a tumor-suppressive role in a variety of cancers [37][38][39], including GC [40,41]. Studies have also reported that long non-coding RNAs (lncRNAs) or circular RNAs (circRNAs) sponge miR-137-3p through a ceRNA mechanism in GC [42,43]. However, no studies have reported that mRNA can regulate miR-137-3p through a ceRNA mechanism, nor has it been reported that miR-137-3p can target COL5A1 or FSTL1.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-137-3p (i.e., miR-137) plays a tumor-suppressive role in a variety of cancers [37][38][39], including GC [40,41]. Studies have also reported that long non-coding RNAs (lncRNAs) or circular RNAs (circRNAs) sponge miR-137-3p through a ceRNA mechanism in GC [42,43]. However, no studies have reported that mRNA can regulate miR-137-3p through a ceRNA mechanism, nor has it been reported that miR-137-3p can target COL5A1 or FSTL1.…”
Section: Discussionmentioning
confidence: 99%
“…miR-137 is targeted by lncRNA NCK1-AS1. Low NCK1-AS1 expression augments the profile of miR-137, reduces that of NUP 43, and represses GC cell proliferation, migration, and invasion [ 51 ]. The inhibitory impact of miR-137 on GC has been substantiated by the above findings.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also reported that long non-coding RNAs (lncRNAs) or circular RNAs (circRNAs) sponge miR-137-3p through a ceRNA mechanism in GC [45][46]. However, no one has reported that mRNA can regulate miR-137-3p through a ceRNA mechanism, nor has it been reported that miR-137-3p can target COL5A1 or FSTL1.…”
Section: Discussionmentioning
confidence: 99%